2013
DOI: 10.1371/journal.pone.0083922
|View full text |Cite
|
Sign up to set email alerts
|

Combining Machine Learning Systems and Multiple Docking Simulation Packages to Improve Docking Prediction Reliability for Network Pharmacology

Abstract: Increased availability of bioinformatics resources is creating opportunities for the application of network pharmacology to predict drug effects and toxicity resulting from multi-target interactions. Here we present a high-precision computational prediction approach that combines two elaborately built machine learning systems and multiple molecular docking tools to assess binding potentials of a test compound against proteins involved in a complex molecular network. One of the two machine learning systems is a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
224
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 331 publications
(224 citation statements)
references
References 43 publications
0
224
0
Order By: Relevance
“…Overall, machine‐learning SFs have exhibited a substantial improvement over classical SFs in different binding affinity prediction benchmarks . Furthermore, a number of studies have shown that a classical SF can easily be improved by substituting their linear regression model with nonparametric machine‐learning regression, either using RF or SVR .…”
Section: Generic Machine‐learning Sfs To Predict Binding Affinitymentioning
confidence: 99%
See 2 more Smart Citations
“…Overall, machine‐learning SFs have exhibited a substantial improvement over classical SFs in different binding affinity prediction benchmarks . Furthermore, a number of studies have shown that a classical SF can easily be improved by substituting their linear regression model with nonparametric machine‐learning regression, either using RF or SVR .…”
Section: Generic Machine‐learning Sfs To Predict Binding Affinitymentioning
confidence: 99%
“…It is noteworthy that this SVR model was trained on the docking poses of a set of known inhibitors, as crystal structures for these ligands were not available. This strategy has also been successfully employed with other SVR models and RF . Given these successes and the very large number of actives that are now known for a range of targets, training on the docking poses of these molecules should strongly increase the size of training sets and thus the performance of machine‐learning SFs.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
See 1 more Smart Citation
“…In spite of these issues, by focusing on the structural features, these docking simulations were able to correctly predict binding modes and the trends in kinase inhibition. Future efforts should focus on three fronts: a) Developing a receptor-based pharmacophore with spatial constraints to include receptor residues as exclusion areas to improve the estimation of binding affinities; b) Inclusion of the impact of conformational changes of key residues in the active site on the estimation of inhibition constant; c) A combined approach of using analytic learning methods along with docking simulations to model cross-reactivity and toxicity [73]. …”
Section: Resultsmentioning
confidence: 99%
“…Based on systems biology and pharmacology, network pharmacology leverages network analysis and screens nodes to identify proteins critical to a disease for drug design [13, 14]. Network pharmacology can be used to investigate synergism of multicomponent drugs to identify high efficacy and low toxicity agents with multiple targets [15, 16].…”
Section: Introductionmentioning
confidence: 99%